The Effect of Body Weight Prior to Molting in Brown Laying Hens on Egg Yield and Quality During Second Production Cycle - Ocak, N.; Sarica, M.; Erener, G.; Garipoglu, A.V. (International Journal of Poultry Science, 2004)
This study focused on the effect of different BW in moulted brown laying hens (Isa-brown) on egg yield and quality during second production cycle. A total of 240 hens after the completion of first production cycle were classified into 4 BW groups; Light (L; 1529-1823 g), Mid-light (ML; 1824-1977 g), Mid-heavy (MH; 1990-2120 g) and Heavy (H; 2124-2797). Groups were consisted of 6 replications and in each replication there were 10 hens reared in individual cages. Moult was induced by feeding hens a commercial compound feed containing high levels of added Zn (15,000 ppm) as Zn oxide during the first 10 days, and following 40 days they were fed laying diet (17% crude protein and 2700 kcal ME/kg; 75 g/day). At the end of moulting period, BW loss was higher (P<0.01) in hens in MH (%17.30) and H (18.42%) groups compared to those in L (11.41%) and ML (11.42%) groups. In second production cycle (147 days), no differences were found among groups in terms of egg yields, but the peak yield of the H hens did not reach those of other groups (P< 0.05). Egg weight of L hens (69.5 g) was lower (P<0.05) than that of ML (70.8 g), MH (71.9 g) and H (71.9 g) hens. Heavy groups had higher feed consumption (P<0.01) and feed conversion ratio (P<0.05) compared to light groups. These results show that mid-light BW of flock prior to molting result in better egg weight, feed consumption and feed conversion ratio in the second production cycle.